(3OQGSGJ GdLOhi GdEbJUGOjI dEJNGP GdbQGQGJ GdESJKeGQjIs - (3YHO GdeWdH(B, (3YHO GdMejOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3GdJYQja HOQGSGJ GdLOhi GdEbJUGOjI(B- (3OQGSGJ GdLOhi GdEbJUGOjI hGdUfGYI GdbQGQGJ GdESJKeGQjI(B- (3CfhGY OQGSGJ GdLOhi GdEbJUGOjI hGdYdGbGJ GdOGNdjI HjfgG(B- (3OQGSI GdLOhi GdHjFjI ddeTQhY(B- (3OQGSI GdLOhi GdbGfhfjI ddeTQhY(B- (3OQGSI GdShb hGdLOhi GdJShjbjI(B- (3Jbjje GdeTQhYGJ ef efXhQ GdEbJUGO Gdbhej(B- (3GdYfGUQ GdCSGSjI dJbQjQ OQGSGJ GdLOhi GdEbJUGOjI hJbjje GdeTQhYGJs
Keywords: (3GJNGP GdbQGQs; (3GdESJKeGQs; (3GdeTQhYGJs